The Influence of Service Quality and System Quality on Branchless Banking Agent Loyalty Mediated by Satisfaction at PT Bank Negara Indonesia (Persero), Tbk in the Work Area of Regional Office 12 - Juni, Ardi Ikhsan; Kunawangsih P., Tri; Hariyanti, Dini (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research was conducted to analyze and study the influence of the Brancless Banking business on PT Bank Negara Indonesia (Persero), Tbk. In the Regional Office 12 Work Area which consists of service quality and system quality on satisfaction and its impact on agent loyalty. The research method used is quantitative research with data analysis techniques using SEM PLS. The research results show that partially or directly (direct effect) everything has a positive and significant influence, namely service quality has an influence on loyalty, system quality has an influence on loyalty, satisfaction has an influence on loyalty, service quality has an influence on satisfaction, and system quality has an influence on satisfaction. Indirectly, satisfaction can mediate significantly positively between service quality and loyalty and satisfaction can mediate significantly positively between system quality and loyalty.